Novel Robot Manipulator Adaptive Artificial Control: Design a Novel SISO Adaptive Fuzzy Sliding Algorithm Inverse Dynamic Like Method. - Sulaiman, Nasri; Piltan, Farzin; Nasiri, Hajar; Allahdadi, Sadeq; Bairami, Mohamad Amin (2011)
Refer to the research, design a novel SISO adaptive fuzzy sliding algorithm inverse dynamic like method